Symptom profile of alcohol withdrawal delirium: factor analysis of Delirium Rating Scale-Revised-98 version. (3rd March 2016) - Grover, Sandeep; Kate, Natasha; Sharma, Akhilesh; Mattoo, Surendra K.; Basu, Debasish; Chakrabarti, Subho; Malhotra, Savita; Avasthi, Ajit
ABSTRACT: Background : The symptom profile of alcohol withdrawal delirium (AWD), relative to deliriums of other etiology, remains uncertain. Objective : To evaluate the factor structure of symptoms in patients with AWD, as assessed by the Delirium Rating Scale-Revised-98 (DRS-R-98). Method : A total of 112 patients aged 18 years or more with AWD were assessed on DRS-R-98. Results : The mean age of participants was 44.2 years. About two-third of the patients developed delirium within 24 hours of the last intake of alcohol and the mean duration of delirium at the time of assessment was 3.9 days. In 46% of cases the delirium was attributed solely to alcohol withdrawal; in the remaining subjects alcohol withdrawal was a major contributory factor. Three separate principal component analysis (whole sample, pure AWD and AWD with associated etiologies) were carried out. In all the factor analyses, one of the factors included cognitive symptoms (attention, orientation and visuospatial disturbances) along with or without short- and long-term memory impairment; the second factor included motoric symptoms along with sleep-wake cycle disturbances; the third factor included psychotic symptoms. For the whole group and subgroup of AWD with associated etiologies, items of higher level thinking (i.e. language disturbances and thought process abnormality) loaded along with cognitive symptoms. In pure AWD group, these items along with memory disturbances loaded with psychotic symptoms. Conclusions : Results of the current factor analyses suggest that the factor structure of pure AWD is different from AWD with associated etiologies. Hence, attention to the symptom profile of patients with AWD may provide clues to delirium etiology.